Microscale hydrogen, carbon, and nitrogen isotopic diversity of organic matter in asteroid Ryugu - Larry R Nittler; Jens Barosch; Katherine Burgess; Rhonda M Stroud; Jianhua Wang; Hikaru Yabuta; Yuma Enokido; Megumi Matsumoto; Tomoki Nakamura; Yoko Kebukawa; Shohei Yamashita; Yoshio Takahashi; et al. (Earth and Planetary Science Letters, 2024)

The thermal history of Ryugu based on Raman characterization of Hayabusa2 samples - Lydie Bonal; Eric Quirico; Gilles Montagnac; Mutsumi Komatsu; Yoko Kebukawa; Hikaru Yabuta; Kana Amano; Jens Barosch; Laure Bejach; George D. Cody; Emmanuel Dartois; Alexandre Dazzi; et al. (Icarus, 2024)

Prevalence of Fragile X-Associated Tremor/Ataxia Syndrome in Patients with Cerebellar Ataxia in Japan - Yujiro Higuchi; Masahiro Ando; Akiko Yoshimura; Satoshi Hakotani; Yuki Koba; Yusuke Sakiyama; Yu Hiramatsu; Yuichi Tashiro; Yoshimitsu Maki; Akihiro Hashiguchi; Junhui Yuan; Yuji Okamoto; et al. (The Cerebellum, 2021)
The presence of fragile X mental retardation 1 ( FMR1 ) premutation has been linked to patients with a certain type of cerebellar ataxia, the fragile X-associated tremor/ataxia syndrome (FXTAS). However, its prevalence in Japan has yet to be clarified. The aim of the present study is to determine the prevalence of FXTAS in Japanese patients with cerebellar ataxia and to describe their clinical characteristics. DNA samples were collected from 1328 Japanese patients with cerebellar ataxia, referred for genetic diagnosis. Among them, 995 patients with negative results for the most common spinocerebellar ataxia subtypes were screened for FMR1 premutation. Comprehensive clinical and radiological analyses were performed for the patients harbouring FMR1 premutation. We herein identified FMR1 premutation from one female and two male patients, who satisfied both clinical and radiological criteria of FXTAS (0.3%; 3/995) as well. Both male patients presented with high signal intensity of corticomedullary junction on diffusion-weighted magnetic resonance imaging, a finding comparable to that of neuronal intranuclear inclusion disease. The female patient mimicked multiple system atrophy in the early stages of her disease and developed aseptic meningitis with a suspected immune-mediated mechanism after the onset of FXTAS, which made her unique. Despite the lower prevalence rate in Japan than the previous reports in other countries, the present study emphasises the necessity to consider FXTAS with undiagnosed ataxia, regardless of men or women, particularly for those cases presenting with similar clinical and radiological findings with multiple system atrophy or neuronal intranuclear inclusion disease.

Differences in fennel seed responses to drought stress at the seed formation stage in sensitive and tolerant genotypes - Ehsaneh Khodadadi; Akiko Hashiguchi; Barat Ali Fakheri; Saeed Aharizad; Abbasali Emamjomeh; Majid Norouzi; Setsuko Komatsu (Journal of Plant Biochemistry and Biotechnology, 2019)

Early Changes in S-Nitrosoproteome in Soybean Seedlings Under Flooding Stress - Akiko Hashiguchi; Setsuko Komatsu (Plant Molecular Biology Reporter, 2018)

Proteomic analysis of temperature dependency of buckwheat seed dormancy and quality degradation - Akiko Hashiguchi; Hiroyuki Yoshioka; Setsuko Komatsu (Theoretical and Experimental Plant Physiology, 2018)

Metabolic profiles of flooding-tolerant mechanism in early-stage soybean responding to initial stress - Xin Wang; Wei Zhu; Akiko Hashiguchi; Minoru Nishimura; Jingkui Tian; Setsuko Komatsu (Plant Molecular Biology, 2017)

Erratum to: Characterization of a novel flooding stress-responsive alcohol dehydrogenase expressed in soybean roots - Setsuko Komatsu; Thibaut Deschamps; Susumu Hiraga; Mikio Kato; Mitsuru Chiba; Akiko Hashiguchi; Makoto Tougou; Satoshi Shimamura; Hiroshi Yasue (Plant Molecular Biology, 2012)

Characterization of a novel flooding stress-responsive alcohol dehydrogenase expressed in soybean roots - Setsuko Komatsu; Deschamps Thibaut; Susumu Hiraga; Mikio Kato; Mitsuru Chiba; Akiko Hashiguchi; Makoto Tougou; Satoshi Shimamura; Hiroshi Yasue (Plant Molecular Biology, 2011)